A comparative study of tunnel / Hadijah Ramsjah - Ramsjah, Hadijah (2005)
A Comparative Study of Tunnel', would be the topic to fulfill the syllabus of Dissertation course, BSV 695. This dissertation is about to study the tunnels' maintenance in Malaysia. Generally, the maintenance issues are related with the previous history of any tunnel. For example, the way the tunnel is constructed as well as its design affected its maintenance, either in short or long term. The lack of supervision at the early stage of developing tunnel makes it to be bad in appearance and due to this, problems will arise. The safety between users will be decreased. In allowing the tunnel to be well-comfort would be created and produced, in order to prevent something bad and unplanned because of insufficient way in providing good tunnel. This facilities and safety features move in parallel to provide more sufficient maintenance program. Comfort tunnel could make the users feel safe, comfort and confidence when they get through it, without any hesitant feeling.